Prospective comparison of gadoxetic acid-enhanced liver MRI and contrast-enhanced CT with histopathological correlation for preoperative detection of colorectal liver metastases following chemotherapy and potential impact on surgical plan. Issue 11 (November 2017) - Jhaveri, Kartik S.; Fischer, Sandra E.; Hosseini-Nik, Hooman; Sreeharsha, Boraiah; Menezes, Ravi J.; Gallinger, Steven; Moulton, Carol-Anne E.
Abstract: Objective: To prospectively compare the diagnostic performance of gadoxetic acid-enhanced MRI (EOB-MRI) and contrast-enhanced CT (CECT) for preoperative detection of colorectal liver metastases (CRLM) following chemotherapy and to evaluate the potential change in the hepatic resection plan. Methods: 51 patients with CRLM treated with preoperative chemotherapy underwent liver imaging by EOB-MRI and CECT prospectively. Two independent blinded readers characterized hepatic lesions on each imaging modality using a 5-point scoring system. 41 patients underwent hepatic resection and histopathological evaluation. Results: 151 CRLM were confirmed by histology. EOB-MRI, compared to CECT, had significantly higher sensitivity in detection of CRLM ≤1.0 cm (86% vs. 45.5%; p < 0.001), significantly lower indeterminate lesions diagnosis (7% vs. 33%; p < 0.001) and significantly higher interobserver concordance rate in characterizing the lesions ≤1.0 cm (72% vs. 51%; p = 0.041). The higher yield of EOB-MRI could have changed the surgical plan in 45% of patients. Conclusion: Following preoperative chemotherapy, EOB-MRI is superior to CECT in detection of small CRLM (≤1 cm) with significantly higher sensitivity and diagnostic confidence and interobserver concordance in lesion characterization. This improved diagnostic performance can alter the surgical plan in almost half of patients scheduled for liver resection.